SCHISTOSOMA MANSONI IN EUNÁPOLIS, BRAZIL: AN INTEGRATED ANALYSIS OF EPIDEMIOLOGICAL, ENVIRONMENTAL, AND MALACOLOGICAL DATA - de Lima, Diana; Rita Kirmse Pereira, Adma; Henrique Paiva Mezete, Kaio; Almeida da Silva, Flaelma (Health and Society, 2025)
Schistosomiasis caused by Schistosoma mansoni remains a significant public health issue in Brazil, particularly in areas with poor sanitation and frequent exposure to contaminated water bodies. In the municipality of Eunápolis, located in southern Bahia, historical records of the disease indicate the persistence of endemic transmission and underreporting in official health information systems. In this context, the present study aimed to carry out an integrated analysis of epidemiological, environmental, and malacological data to identify risk factors for the maintenance and possible reactivation of the schistosomiasis transmission cycle in the region. This is an observational, cross-sectional study with a quantitative-qualitative approach, conducted between 2023 and 2024. Secondary data were collected from SINAN, SIAB, and DATASUS, as well as primary data obtained through physicochemical and microbiological analyses of water samples and malacological surveys at 11 strategic points in the municipality. The results revealed the presence of fecal coliforms in water bodies used for bathing and recreation, along with the identification of Biomphalaria snails in areas of frequent human activity. The analyses highlight the coexistence of environmental and social factors that contribute to vulnerability to schistosomiasis, underscoring the need for intersectoral control actions, improved sanitation, and health education.